2020
DOI: 10.21203/rs.3.rs-110462/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-diagnostic Circulating Concentrations of Fat-soluble Vitamins and Risk of Glioma in Three Cohort Studies

Abstract: Few prospective studies have evaluated the relation between fat-soluble vitamins and glioma risk. Using three cohorts—UK Biobank (UKB), Nurses’ Health Study (NHS), and Health Professionals Follow-Up Study (HPFS), we investigated associations of pre-diagnostic concentrations of fat-soluble vitamins D, A, and E with incident glioma. In 346,785 participants (444 cases) in UKB, associations with vitamin D (25-hydroxyvitamin D [25(OH)D]) were evaluated by Cox proportional hazards regression. In NHS (52 cases, 104 c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In contrast, a metabolomic analysis revealed a positive link between both α-and γ-tocopherols in the sera and the risk of glioblastoma [17]. In a recent report, Yue et al showed an insignificant positive association between α-and γ-tocopherols in the sera and the risk of glioma [103]. In a survey of 470 glioblastoma patients, Mulpur and colleagues found that complementary therapy with vitamin E non-significantly increases mortality [104].…”
Section: Vitamin Ementioning
confidence: 98%
“…In contrast, a metabolomic analysis revealed a positive link between both α-and γ-tocopherols in the sera and the risk of glioblastoma [17]. In a recent report, Yue et al showed an insignificant positive association between α-and γ-tocopherols in the sera and the risk of glioma [103]. In a survey of 470 glioblastoma patients, Mulpur and colleagues found that complementary therapy with vitamin E non-significantly increases mortality [104].…”
Section: Vitamin Ementioning
confidence: 98%